The Knowledge Of Oral Antibiotics Use In Students Of STIKES Dirgahayu Samarinda - Demitha Darius (Unit Penelitian dan Pengabdian Kepada Masyarakat (UPPM) STIKES Dirgahayu Samarinda, 2023)
There are still errors in the use of antibiotics that are a risk for antibiotic resistance. The level of knowledge affects the correct use of antibiotics, especially for students who take health education are expected to have a good level of knowledge in order to minimize the risk of antibiotic resistance. The aims of the study were to determine the knowledge of STIKES Dirgahayu Samarinda students about the use of oral antibiotics, to determine the effect of respondents' characteristics on the level of knowledge of oral antibiotics and to determine the relationship between the level of knowledge and the use of oral antibiotics without a doctor's prescription. The research method used is descriptive observational and cross sectional. The results showed that the level of knowledge about oral antibiotics in S1 Pharmacy students of STIKES Dirgahayu Samarinda was in the good category, namely the average total score was 15. There was no relationship between age, gender, place of origin and level with the level of knowledge of oral antibiotics of respondents with p value > alpha (0.05). There is no relationship between the level of knowledge and the use of oral antibiotics without a doctor's prescription with a p value > alpha (0.05).